A Functional Study of AUXILIN-LIKE1 and 2, Two Putative Clathrin Uncoating Factors in Arabidopsis - Adamowski, Maciek; Narasimhan, Madhumitha; Kania, Urszula; Glanc, Matouš; De Jaeger, Geert; Friml, Jiří (The Plant cell, 2018)
Clathrin-mediated endocytosis (CME) is a cellular trafficking process in which cargoes and lipids are internalized from the plasma membrane into vesicles coated with clathrin and adaptor proteins. CME is essential for many developmental and physiological processes in plants, but its underlying mechanism is not well characterized compared with that in yeast and animal systems. Here, we searched for new factors involved in CME in Arabidopsis thaliana by performing tandem affinity purification of proteins that interact with clathrin light chain, a principal component of the clathrin coat. Among the confirmed interactors, we found two putative homologs of the clathrin-coat uncoating factor auxilin previously described in non-plant systems. Overexpression of AUXILIN-LIKE1 and AUXILIN-LIKE2 in Arabidopsis caused an arrest of seedling growth and development. This was concomitant with inhibited endocytosis due to blocking of clathrin recruitment after the initial step of adaptor protein binding to the plasma membrane. By contrast, auxilin-like1/2 loss-of-function lines did not present endocytosis-related developmental or cellular phenotypes under normal growth conditions. This work contributes to the ongoing characterization of the endocytotic machinery in plants and provides a robust tool for conditionally and specifically interfering with CME in Arabidopsis.
Keywords: endocytóza; proteiny huseníčku; Protein Binding; Protein Transport; klathrin; vazba proteinů; semenáček; Arabidopsis Proteins; Clathrin; Endocytosis; Seedlings; transport proteinů; Arabidopsis